2019
DOI: 10.1007/s00167-019-05729-3
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of mesenchymal stem cells in combination with allogenic cartilage improves cartilage regeneration and clinical outcomes in patients with concomitant high tibial osteotomy

Abstract: Purpose This study aimed to compare the clinical, radiological, and second‐look arthroscopic outcomes of implanting mesenchymal stem cells (MSCs) alone and together with allogenic cartilage in patients treated with concomitant high tibial oteotomy (HTO) for varus knee osteoarthritis. Methods Eighty patients treated with cartilage repair procedures and concomitant HTO were prospectively randomized into two groups: MSC implantation (MSC group), and MSC implantation with allogenic cartilage (MSC‐AC group). Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 45 publications
1
44
0
1
Order By: Relevance
“…In this review we identified six randomized, double-blinded, placebo-controlled trials, including one follow-up study [64][65][66]78,105,109], eight randomized controlled trials [67][68][69]79,[81][82][83]103] and two prospective, randomized cohort studies [70,84]. Most studies were however prospective uncontrolled clinical trials, comparative matched pair analyses, retrospective comparative studies or retrospective case series and an inter-study comparison was difficult due to the variance in study design.…”
Section: Study Designs and Route Of Cell Deliverymentioning
confidence: 99%
See 4 more Smart Citations
“…In this review we identified six randomized, double-blinded, placebo-controlled trials, including one follow-up study [64][65][66]78,105,109], eight randomized controlled trials [67][68][69]79,[81][82][83]103] and two prospective, randomized cohort studies [70,84]. Most studies were however prospective uncontrolled clinical trials, comparative matched pair analyses, retrospective comparative studies or retrospective case series and an inter-study comparison was difficult due to the variance in study design.…”
Section: Study Designs and Route Of Cell Deliverymentioning
confidence: 99%
“…Local application was either achieved through simple intra-articular injections of MSCs mixed with saline [64,66,99,103,104,110] or PRP [69,70,81,87,89,93,96,97]. Implantation of MSCs was further supported by allogenic cartilage [84], or the use of fibrin glue scaffolds [85,91,94]. Park et al used drill holes [104] and other groups combined MSC applications with surgical correction operations like HTO for knee OA [81,84,86] or lateral sliding calcaneal osteotomy for ankle OA [88].…”
Section: Study Designs and Route Of Cell Deliverymentioning
confidence: 99%
See 3 more Smart Citations